Synthesis and Crystal Structure of a Two-Dimensional Zn(II) Coordination Polymer - Zhou, Lianwen (Asian Journal of Chemistry, 2011)
A new coordination polymer [Zn2(PAA)2(bib)]n (H2PAA= phthalic acid and bib= 4,4'-bis(2- methylimidazol-1-ylmethyl)biphenyl) has been synthesized by the hydrothermal method and characterized by X-ray single crystal diffraction. In compound [Zn2(PAA)2(bib)]n, the phthalic acid acts as bridging ligands exhibiting two coordination modes to link metal ions: bis-monodentate and monoatomic bridging modes. The carboxylic groups bridge Zn(II) ions to an infinite one-dimensional framework. 4,4'-Bis(2-methylimidazol-1-ylmethyl)biphenyl) ligands coordinate to two Zn(II) centers to give rise to a two-dimensional net.